Upaya Meningkatkan Keterampilan Menulis Puisi dengan Penggunaan Media Video pada Siswa Kelas II SDIT Al-Fashih - Khoerunnisa, Putri (Lembaga Yasin AlSys, 2022)
This research is a type of Classroom Action Research (CAR) which was carried out in 2 cycles, each cycle consisting of 3 meetings. The research subjects were all second grade students of SDIT AL-FASIH with a total of 13 students, consisting of 6 boys and 7 girls. The procedure for implementing each cycle includes planning, implementing, observing, and reflecting. Data collection was obtained from teacher and student observation sheets, student poetry writing skills assessment sheets and documentation. Based on the results of the study, it can be concluded that the first is that there is an increase in the results of poetry writing skills using video media in class II SDIT AL-FASHIH students, this is evidenced by the results in the initial conditions before the action, namely with an average value of 65.38 or only 4 people whose score is reach KKM. In the first cycle there was an increase with an average value of 78.08 or 9 people whose scores reached the KKM. In the second cycle, it increased with an average value of 83.38 or 11 people whose scores reached the KKM. Second, improving the quality of the learning process for poetry writing skills using video media for class II SDIT AL-FASHIH students. The improvement in the quality of the learning process can be proven from the improvement in the learning process and teacher performance. The increase in teacher performance was proven in the average value of the first cycle of 77, while the second cycle with the average value of 84. The improvement in the learning process of writing poetry was evident in the average value obtained in each cycle. Thus, video media can be used to improve poetry writing skills in second grade students of SDIT AL-FASHIH.